Hydrogeophysical Characterization in a Volcanic Context From Local to Regional Scales Combining Airborne Electromagnetism and Magnetism. Issue 12 (12th June 2021) - Dumont, M.; Reninger, P. A.; Aunay, B.; Pryet, A.; Jougnot, D.; Join, J. L.; Michon, L.; Martelet, G.
Abstract: In volcanic islands, a crucial step in managing watershed water resources is the characterization of groundwater aquifers from local to regional scales. Airborne geophysical data provide high‐resolution images down to hundreds of meters below the surface, over large areas. Yet, the production of an accurate interpretation of regional geophysical imagery may be time consuming or limited by the low density of geological and hydrological field observations. Here, we propose an approach combining airborne electromagnetic and magnetic data in order to reduce geophysical ambiguities and provide a multiscale hydrogeophysical characterization of Piton des Neiges volcano (Réunion Island). With limited calibration data, this methodology produces a geological model more accurate than using airborne electromagnetic data alone. Through the continuous coverage of both methods, we demonstrate the influence of volcanic unit geometries on groundwater flows within the critical zone and we highlight major structures impacting groundwater flows at both local and regional scales. Plain Language Summary: Groundwater characterization from local to regional scale is an essential element especially for sustainable water policy. In volcanic settings, the complexity of the subsurface and geological structures is still poorly integrated into hydrological models, leading to uncertainties in predictive models. Our study aims to combine two geophysical methods acquired during airborne surveys over Réunion Island in order to (a) improve the accuracy of airborne geophysical image interpretation without limited external information, (b) characterize structures and their influences on groundwater flows, and (c) upscale these results from local to regional scales. The methodology may be applied to other complex geological settings in order to integrate local and regional heterogeneities into hydrological models. Key Points: Magnetic measurements help constrain the hydrological interpretation of resistivity models in volcanic settings Hydrogeophysical interpretations of deep airborne electromagnetic imaging unveil groundwater stratified flows between volcanic units Coupled analysis of airborne electromagnetic and magnetic data sets allows us to improve groundwater management from local to regional scale